Adsorption properties of acrolein, propanal, 2-propenol, and 1-propanol on Ag(111). Issue 43 (28th October 2020) - Muir, Mark; Molina, David L.; Islam, Arephin; Abdel-Rahman, Mohammed K.; Trenary, Michael
Abstract : The properties of acrolein and its hydrogenation products, 2-propenol, propanal, and 1-propanol adsorbed on Ag(111) at 85 K were determined. Abstract : Reflection absorption infrared spectroscopy and temperature programmed desorption were used to study the adsorption of acrolein, its partial hydrogenation products, propanal and 2-propenol, and its full hydrogenation product, 1-propanol on the Ag(111) surface. Each molecule adsorbs weakly to the surface and desorbs without reaction at temperatures below 220 K. For acrolein, the out-of plane bending modes are more intense than the CO stretch at all coverages, indicating that the molecular plane is mainly parallel to the surface. The two alcohols, 2-propenol and 1-propanol, have notably higher desorption temperatures than acrolein and display strong hydrogen bonding in the multilayers as revealed by a broadened and redshifted O–H stretch. For 1-propanol, annealing the surface to 180 K disrupts the hydrogen-bonding to produce unusally narrow peaks, including one at 1015 cm −1 with a full width at half maximum of 1.1 cm −1 . This suggests that 1-propanol forms a highly orderded monolayer and adsorbs as a single conformer. For 2-propenol, hydrogen bonding in the multilayer correlates with observation of the CC stretch at 1646 cm −1, which is invisible for the monolayer. This suggests that for monolayer coverages, 2-propenol bonds with the CC bond parallel to the surface. Similarly, the CO stretch of propanal is very weak for low coverages but becomes the largest peak for the multilayer, indicating a change in orientation with coverage.